Importing U.S. Exchange Rate Data from the Federal Reserve and Standardizing Country Names across Datasets. (July 2013) - Dicle, Betul; Levendis, John; Dicle, Mehmet F.
Fxrates is a command to import historical U.S. exchange rate data from the Federal Reserve and to calculate the daily change of the exchange rates. Because many cross-country datasets use different spellings and conventions for country names, we also introduce a second command, countrynames, to convert country names to a common naming standard.